School times in a time of pandemic and necropolitics (Práxis Educativa, 2020)
The present text is inspired by a live presented with Maura Corcini, organized by the National Association of Graduate Studies and Research in Education (ANPEd). It has four sections. The first section, “The necrology, the pandemic, Brazil”, describes the way in which the Bolsonarist government develops a necropolitics, including from the tragic COVID-19 pandemic that is currently expanding throughout Brazil and the world. The second section, “Education, between necropolitics and pandemic”, announces two dimensions of this same pandemic and what it allows us to perceive in relation to school, as an institution and as a form. The third section, “The Pandemic and the school times”, presents the specificity of three educational times: chronos, kairos and aion. Finally, the last section, “The time of childhood: Isabel(a) and the unpredictable time of reading and writing” resumes a childlike inspiration and some senses that emanate from it to remember the value and meaning of childhood in education.Keywords: Time. School. Necropolitics.